Knowledge Level of Gracia Sustain Foundation TK/SD Medan Teachers about Acute Otitis Media - Siahaan, Maranatha Duva; Ashri Yudhistira; Sabri (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
Background. Acute Otitis Media (AOM) is a rapidly developing inflammatory condition within the middle ear that commonly occurs in children. Kindergarten / elementary school teachers educate children who may also have indications of AOM, so if these teachers have a sufficient level of knowledge about AOM, it will be easier to identify and especially prevent it. This study set intended to investigate parents' attitudes and knowledge on treating their children's acute otitis media Methods. This study is a descriptive study that uses a cross-sectional analytic approach. Sampling was done using the total sampling method using a questionnaire. The research subjects were 70 teachers at Yayasan Gracia Sustain kindergarten/primary school in Medan. Data were analyzed using the SPSS version 25 application. Results. The results of the analysis of 70 teachers at Yayasan Gracia Sustain kindergarten/primary school Medan showed that 7 teachers (10.0%) had good knowledge, 63 teachers (90.0%) had moderate knowledge, and no teachers had low knowledge. Conclusion. The teachers of Yayasan Gracia Sustain kindergarten/primary school in Medan have a moderate level of knowledge about AOM.